TGF-β2 silencing to target biliary-derived liver diseases - Dropmann, Anne; Dooley, Steven; Dewidar, Bedair; Hammad, Seddik; Dediulia, Tatjana; Werle-Urban, Julia; Hartwig, Vanessa; Ghafoory, Shahrouz; Wölfl, Stefan; Korhonen, Hanna; Janicot, Michel; Wosikowski, Katja; et al. (Gut, 2020)
Objective TGF-β2 (TGF-β, transforming growth factor beta), the less-investigated sibling of TGF-β1, is deregulated in rodent and human liver diseases. Former data from bile duct ligated and MDR2 knockout (KO) mouse models for human cholestatic liver disease suggested an involvement of TGF-β2 in biliary-derived liver diseases. - Design As we also found upregulated TGFB2 in liver tissue of patients with primary sclerosing cholangitis (PSC) and primary biliary cholangitis (PBC), we now fathomed the positive prospects of targeting TGF-β2 in early stage biliary liver disease using the MDR2-KO mice. Specifically, the influence of TgfB2 silencing on the fibrotic and inflammatory niche was analysed on molecular, cellular and tissue levels. - Results TgfB2-induced expression of fibrotic genes in cholangiocytes and hepatic stellate cellswas detected. TgfB2 expression in MDR2-KO mice was blunted using TgfB2-directed antisense oligonucleotides (AON). Upon AON treatment, reduced collagen deposition, hydroxyproline content and αSMA expression as well as induced PparG expression reflected a significant reduction of fibrogenesis without adverse effects on healthy livers. Expression analyses of fibrotic and inflammatory genes revealed AON-specific regulatory effects on Ccl3, Ccl4, Ccl5, Mki67 and Notch3 expression. Further, AON treatment of MDR2-KO mice increased tissue infiltration by F4/80-positive cells including eosinophils, whereas the number of CD45-positive inflammatory cells decreased. In line, TGFB2 and CD45 expression correlated positively in PSC/PBC patients and localised in similar areas of the diseased liver tissue. - Conclusions Taken together, our data suggest a new mechanistic explanation for amelioration of fibrogenesis by TGF-β2 silencing and provide a direct rationale for TGF-β2-directed drug development.
Gesehen am 26.02.2021